Pope's Chapel United Methodist Church Forty-Fifth Annual Homecoming, October 7, 2001 - (:unkn) unknown (Wilkes County, Georgia: Pope's Chapel First Methodist Church)
Pope's Chapel United Methodist Church Forty-Fifth Annual Homecoming, October 7, 2001. Kathy Morris, pastor. Event program and invitation. Pope's Chapel First Methodist Church. Wilkes County, Georgia. United States.
1 electronic document. popes-chapel_program_20011007.pdf. 5 pages. 28551276 bytes (master).
Keywords: Church history; Congregational churches; Homecoming; Methodist Church--Anniversaries, etc.; Methodists; Pope's Chapel United Methodist Church (Wilkes County, Ga.); Programs (Publications); United Methodist Church (U.S.); Wilkes County (Ga.); Georgia; Asbury, Francis; Bamford, Sophia; Boyd, James W; Burton, Debbie; Cash, M.T.; Chafin, David; Chafin, Elizabeth; Chafin, Malcolm; Combs, Hazel; Faulk, Nanci Norman; Fortson, Benjamin Winn; Fortson, Rebecca Olivia; Fortson, Warren; Harris, Lundye; Humphries, Thomas; Keen, John; Landrum, John; Morris, Kathy; Neal, Augustus A.; Norman, Ben; Norman, Jimmy; Ogilvie, Hannah Rebecca; Pope, Henry; Slaton, Betty; Slaton, Marion; Slaton, Russell; Slaton, Willie Belle; Smith, George; Truitt, Alfred; Walton, Andrea; Wiggins, Tom